The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China - Liu, Sheng-Nan; Tang, Liang; Luo, Yong-Ting (Zootaxa, 2018)
Species of the Stenus cirrus group in Fujian Province, East China, are reviewed and two new species are described: S. mangdangshanus sp. n. and S. fujianensis sp. n. The females of S. cooterianus Puthz, 2003 and S. wuyiensis Puthz, 2003 are discovered and illustrated for the first time. The diagnostic characters of the new species are illustrated, and a key to species of the Stenus cirrus group of Fujian Province is provided.